Design and Analysis of Intelligent Home System for Remote Control of Luminance by Mobile Terminal. (June 2020) - Zhai, Dong; Li, HongWei
Abstract: Nowadays, the Internet provides a strong technical support for the construction and development of smart home.Smart home sets the user's living environment as the central platform, and USES many technologies such as Internet of things, radio frequency identification, etc., to practice the unification, intelligent management and regulation of all indoor household appliances, which has obviously improved people's living quality and created convenient conditions for users to manage household appliances.Under the pressure of high technology, the current smart home products on the market are of various types, diverse functions, each has its own advantages, most of the products are mainly used to regulate the switch quantity, analog quantity control involved in the degree of insufficient, unable to achieve the indoor lighting degree of fast and accurate regulation.This paper mainly develops a remote control system based on Android mobile terminal, and explores the specific method for the system to control the brightness of smart home lamps, so as to further improve the level of intelligence of smart home and the satisfaction of residents.